2000
DOI: 10.1007/s002680010200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Mechanisms Regulating Drug Sensitivity and the Development of New Chemotherapy Strategies for Genitourinary Carcinomas

Abstract: The emergence of drug-resistant tumors during treatment remains one of the major obstacles in cancer chemotherapy. Overexpression of P-glycoprotein encoded by the multidrug resistance 1 (MDR1) gene or multidrug resistance-associated protein (MRP) (or both) and decreased expression of DNA topoisomerase II are responsible for expression of the multidrug resistance (MDR) phenotype. The expression of P-glycoprotein is also often observed in untreated cancers showing spontaneous MDR, such as renal cell carcinoma. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…cisplatin resistance is thought to be complex and multicausal phenomenon. Many resistance-related molecules including detoxifying enzymes, drug-efflux pumps, DnA repair enzymes and apoptosis-related genes have been reported (26,27). In this study, we identified that ENTPD6 may be a factor determining cisplatin sensitivity in testicular cancer.…”
Section: Discussionmentioning
confidence: 66%
“…cisplatin resistance is thought to be complex and multicausal phenomenon. Many resistance-related molecules including detoxifying enzymes, drug-efflux pumps, DnA repair enzymes and apoptosis-related genes have been reported (26,27). In this study, we identified that ENTPD6 may be a factor determining cisplatin sensitivity in testicular cancer.…”
Section: Discussionmentioning
confidence: 66%
“…Because one of the major mechanisms of resistance is that mediated by export proteins, several inhibitors of these pumps have been investigated. However, clinically relevant chemosensitizing doses of the currently available reversal agents cannot be given to humans without significant side effects (Naito et al, 2000). An alternative to the functional blocking of exporting pumps is enhancing drug specificity toward tumor cells to reach intracellular concentrations of the active agent enough to carry out its cytostatic effect.…”
mentioning
confidence: 99%
“…As >80% of RCCs express the phenotype of multidrug resistance, chemotherapy is rarely efficient. [4][5][6] However, RCCs are supposed to be immunogenic; 7-11 hence, immunotherapeutic strategies are dominant. should be mentioned.…”
mentioning
confidence: 99%
“…As >80% of RCCs express the phenotype of multidrug resistance, chemotherapy is rarely efficient. [4][5][6] However, RCCs are supposed to be immunogenic; [7][8][9][10][11] hence, immunotherapeutic strategies are dominant. [12][13][14][15] Application of IL-2, [16][17][18][19][20] IFN-a [21][22][23][24] or the combination of IL-2 plus IFN-a [25][26][27][28] also together with fluorouracil and vinblastine 29 have been reported to significantly improve the 3-year survival rate.…”
mentioning
confidence: 99%